Produção de sínter com pellet screenings e pellet feed com emprego de granulação intensiva - Helio Cardoso Pereira (2015)
Pilot sintering tests were performed in order to compare production parameters and quality of sinters produced based on Western Europe and Asia standard mixtures, with sinters produced from the addition of Samarcos pellet feed and pellet screenings, that substituted part of the ore in the standard mixture, under four different conditions. Samarco pellet feed in Western Europes standard mixture For additions of 10% and 20% of Samarcos pellet feed without pre-agglomeration, there was a drop in productivity of the sinter. However, it was possible to achieve maximum productivity in the sinter plant, with the addition of 30% of pellet feed pre-agglomerated in an intensive mixer with addition of 10% of hydrated lime, by replacing other ores from the standard mixture studied. With the addition of the pre-agglomerated pellet feed it was possible to reduce energy consumption and achieve good results on sinters metallurgical characteristics. Pellet feed in Asias standard mixture For additions of 10% and 20% of the pellet feed without pre-agglomeration, there was a drop in productivity of the sinter. With the addition of pellet feed pre-agglomerated in an intensive mixer with addition of 10% hydrated lime, by substituting other ores from the standard mixture studied, it was not obtained productivity gain for additions of 30% and 40%. There was a small gain when adding 20%. However, with the addition of the pre-agglomerated pellet feed, it was possible to reduce energy consumption and achieve good results in physical and metallurgical characteristics. Pellet screenings in Western Europes standard mixture It was achieved high productivity in the sinter, with the addition of pellet screenings from 10% to 40% by substituting the other ores from the mixture studied. A level of 40% addition of pellet screenings increased the yield value of the sinter plant 6.6t/m2.24h or 19.13%, superior to that was achieve with the standard mixture. With the addition of pellet screenings, it was possible to reduce energy consumption with good results in the sinters physical and metallurgical characteristics.Pellet screenings in Asians standard mixture It was possible to achieve a high productivity in the sinter, with the addition of pellet screenings from 10% to 40% replacing other ores from the standard mixture studied. A level of 40% addition of pellet screenings increased the yield value of the sinter plant by 6.6t / m2.24h or 20.50%, superior to the result achieved with the standard mixture. With the addition of pellet screenings it was possible to reduce energy consumption with good results in the sinters physical and metallurgical characteristics.